Indole Diketopiperazine Alkaloids Isolated From the Marine-Derived Fungus Aspergillus chevalieri MCCC M23426 - Lv, Dongli; Xia, Jinmei; Guan, Xiaoqing; Lai, Qiliang; Zhang, Beibei; Lin, Jianhui; Shao, Zongze; Luo, Sulan; Zhangsun, Dongting; Qin, Jiang-Jiang; Wang, Weiyi (Frontiers in Microbiology, 2022)
Two new indole diketopiperazines (1–2), were characterized from the fermentation culture of a deep-sea-derived fungus Aspergillus chevalieri MCCC M23426, together with nine biogenetic related compounds (3–11). The structures of 1–2 were assigned based on NMR, MS, NMR calculation, DP4+ analysis, and ECD calculation. In the bioactive assay, 1, 5–7 significantly inhibited the growth of Staphylococcus aureus. Meanwhile, compound 8 potently reduced cell viability in gastric cancer cell MKN1 with an IC50 value of 4.6 μM.